Art et féminisme. - Arbour, Rose Marie; Dallier, Aline; Dubreuil-Blondin, Nicole; Foisy, Suzanne; Guay, Diane; Lamoureux, Johanne; Lamy, Suzanne; Saint-Gelais, Thérèse; Musée d'Art Contemporain, Montréal (Québec : Ministère des Affaires culturelles, 1982)
Abbott, Louise ; Bernatchez, Elise ; Bilodeau, Louise ; Brochu, Andrée ; Chouinard, Marie ; Cohen, Sorel ; Coulombe, Carmen ; Cournoyer, Michèle ; Crawley, Judith ; Dagenais, Lorraine ; Décary, Marie ; Nantel, Lise ; Falardeau, Mira ; Gauthier-Mitchell, Louisette ; Greenberg, Sheila ; De Grosbois, Louise ; de Guise, Anne ; Gutsche, Clara ; Guttman-Bain, Freda ; etc.
Art et féminisme, Musée d'Art Contemporain, Montréal, 11 mars - 2 mai 1982
boek